Effect of Motivation and Job Satisfaction on Teacher Performance in Private Madrasah Aliyah in Maros Regency - Fadliyana Nur; Ulfiani Rahman; Musdalifa Musdalifa (Program Pascasarjana Universitas Negeri Makassar, 2019)
This study aims to determine and analyze the effect of motivation and job satisfaction on teacher performance at the Maros Regency Private Madrasah Aliyah. The type of research used was quantitative with the ex post facto method and data management techniques were analyzed descriptively and inferentially. The instrument is a questionnaire that has been tested for validity and reliability. The sample in this study were 116 private Madrasah Aliyah teachers in Maros Regency whose research was conducted in December 2018 - February 2019. The results of the study revealed that the effect of motivation and job satisfaction had a significant effect on the performance of Private Madrasahs in Maros Regency. That is, work motivation must be increased so that it can affect teacher performance. If job satisfaction is increased, the motivation of teacher work must be increased. Together, motivation and job satisfaction have a significant effect on teacher performance in maros district.